Evaluation of relationship between noise-induced hearing loss with age and work duration in tile industry - Z Loukzadeh; F Foroughinasab; B Saranjam; A ShojaaddinyArdekani; R Soltani (طب کار)
Abstract Background: Noise is a harmful environmental factor which may cause hearing loss, hypertension, and higher rates of occupational accidents and reduced production. Considering the various intensities and frequencies produced by industrial equipments, we assessed the effects of noise on hearing of tile industry workers. Methods: This cross-sectional study was done on 372 workers exposed to noise level of ≥85 dB in a tile factory in Yazd. After clinical examination and completing the questionnaire, audiometry was done by an audiologist for all. Data was then analyzed using SPSS software. Results: Our data showed mean age and work duration was 32.2 ± 6.9 and 9.5 ± 6.4 years respectively. Mean hearing thresholds for both ears were higher in 4000 and then 8000 Hz, as well as in higher frequencies rather than lower ones. Also, left ear showed more sensitivity than right ear. There was a significant relationship between hearing threshold and age and work duration (p<0.001). Conclusion: Our findings showed that exposure to noise in tile industry increases mean hearing thresholds in higher frequencies especially for 4000 Hz, while age and work duration are important factors.